Radiocarbon Dating for the Reconstruction of the 1717 CE Triolet Rock Avalanche in the Mont Blanc Massif, Italy - Hajdas, Irka; Sojc, Ursula; Ivy-Ochs, Susan; Akçar, Naki; Deline, Philip (Frontiers in Earth Science, 2021)
The Arp Nouva peat bog located in the upper Ferret Valley in the Mont Blanc massif was critically evaluated since published radiocarbon dates have led to controversial conclusions on the formation of this swamp. Radiocarbon dating of woody fragments from three pits of up to 1 m depth was used to discuss the question of whether the historically documented rock avalanche occurring in 1717 CE overran the peat bog or settled prior to its formation. For the deepest samples in the pits, ages between 1652 and 1950 CE were obtained, which fit very well into the time frame of the historical documented 1717 CE rock avalanche event. It can, therefore, be concluded that the Arp Nouva peat bog was formed by blockage of the Bella Combe torrent by the rock avalanche deposits. Furthermore, careful sample preparation with consequent separation of roots from the bulk peat sample has shown that the problem of too old 14 C ages can be circumvented. This work demonstrates that a combined geomorphological and geochronological approach is the most reliable way to reconstruct landscape evolution. The key to successful 14 C dating is careful sample selection and the identification of the material that might not be ideal for chronological reconstructions.